El impacto de la ley 142 de 1994 en el sistema tarifario de servicios públicos, en las empresas que prestan el servicio de agua potable (2020)
In this investigativa-formativa activity the main interest is to show to the situation of the communitarian aqueducts and the companies of services public, in this case the Cestillal aqueduct Diamante and the company Aguas and Aguas de Pereira, before and after the application of 1994 law 142. The approach becomes, by means of three theoretical perspective: the economic one, the financier and the administrative one, looking for to include/understand the operation of the water, its handling and its importance as I publish well.